How do parents perceive the returns to parenting styles and neighborhoods? - Lukas Kiessling (Max Planck Institute for Research on Collective Goods, 2020)
This paper studies parental beliefs about the returns to two factors affecting the development and long-term outcomes of children: (i) parenting styles defined by the extent of warmth and control parents employ in raising children, and (ii) neighborhood quality. Based on a representative sample of 2,119 parents in the United States, I show that parents perceive large returns to the warmth dimension of parenting as well as neighborhood quality, and document that parenting is perceived to compensate for the lack of a good environment. Mothers expect larger returns than fathers, but there is no socioeconomic gradient in perceived returns despite a high degree of heterogeneity. Furthermore, I introduce a measurement error correction by leveraging beliefs measured in two different domains, and show that parents' perceived returns relate to their actual parenting styles. My results suggest that parental beliefs are an important determinant of parental decision-making, but cannot explain socioeconomic differences in parenting.
Keywords: I24; I26; J13; J24; D19; R23; 330; Beliefs; Parenting styles; Neighborhoods; Child outcomes; Human capital